Congenital Gastric Outlet Obstruction and Nonimmune Hydrops Fetalis: A Prenatal Sonographic Diagnosis of a Case with Hydrothorax and Ascites - A. Yisau Abdulkadir; O. A. M. Adesiyun; A. Adisa Fawole; A. Peter Aboyeji (The Scientific World Journal)
A case of a male fetus with sonographic diagnosis of hydrops fetalis at 19-week gestation is reported. The fetus had anasarca, bilateral massive pleural effusion, and ascites, in addition to cardiac arrhythmia and congenital gastric outlet obstruction. Mother's clinical history and laboratory workup excluded immune hydrops. The etiological dilemma and fetal outcome are discussed. We concluded, based on this case, that when fetal hydrops occurs early and is associated with multiple congenital anomalies, prolonging the pregnancy may be futile.